A valorização da arte na escola: a EXPOARTE como experiência pedagógica. - LEMOS, Jacqueline Bezerra Ferreira (2020)
This article presents a reflection on the practice of a pedagogical proposal developed at the basic education unit Ministro Henrique de La Roque in Paço do Lumiar – MA. That derives from experience developed through an occupation project that we call SALA 12 DE TEATRO, which has EXPOARTE as the culmination of this proposal. Our objective was to demonstrate that the active occupation of the school environment can occur through Art projects and that this is a viable intervention possible to be shared and that contributes to the valorization of art in education. We present the practices that consolidated in our school - student leadership, education through research and guarantee of the student's autonomy in their learning process in art, in the construction of an event of culmination that occupied the school. Methodologically, we followed the path of research, of an exploratory, qualitative and empirical character. The theoretical framework that supports the experience enunciated in this scientific production has as main interlocutors: SANTANA (2012), who shows us the path taken by Art-Education in its consolidation process at school, Jonh Dewey (2010) who reflects how the experience in art education. BARBOSA (2007), who clarifies a possibility of methodology in art, Pedro Demo (2015) who instrumentalizes the practice of research at school, Paulo Freire (2011) who gives the teacher the means to promote a pedagogy of autonomy, Sousa (2012) who highlights the importance of student leadership and BNCC (2020) which recommends a curriculum in art that is more critical, creative and contextualized. The instruments analyzed in this research were: interviews, logbooks, written tests or, as we call it, Experience Reports. The evaluation of the content produced by the students, made in the light of the authors, helps us to rediscover the place of Art in the school, reaffirming that this place exists in the physical space, in the curriculum, the school calendar, can be expanded based on the Culminance projects.